2016
DOI: 10.3233/efi-160983
|View full text |Cite
|
Sign up to set email alerts
|

The use of technology in group-work: A situational analysis of students' reflective writing

Abstract: Article ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 52 publications
2
17
1
Order By: Relevance
“…This included delays of immediate responses when required. In a study done by McKinney and Sen (2016), similar findings were reported where groups used electronic devices (such as smart phones).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This included delays of immediate responses when required. In a study done by McKinney and Sen (2016), similar findings were reported where groups used electronic devices (such as smart phones).…”
Section: Discussionsupporting
confidence: 71%
“…Success of group work, although empirically reported (Cartwright et al 2021;McKinney and Sen 2016), may not always be constant as contextual dynamics may differ. There is a difference between working in a group, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations